Hong Kong Documentary Film - Aitken, Ian (Edinburgh University Press, 2022)
GBS_insertPreviewButtonPopup(['ISBN:9780748664696','ISBN:9780748664702','ISBN:9780748664726']);A comprehensive study of the lost genre of Hong Kong documentary filmRead and download the first chapter for free here (pdf)Does Hong Kong have a significant tradition in documentary filmmaking? Until recently, many film scholars believed not. Yet, when Ian Aitken and Michael Ingham challenged this assumption, they discovered a rich cinematic tradition, dating back to the 1890s.Under-researched and often forgotten, documentary film-making in Hong Kong includes a thriving independent documentary film movement, a large archive of documentaries made by the colonial film units, and a number of classic British Official Films. Case studies from all three categories are examined in this book, including The Battle of Shanghai, The Sea and the Sky, Rising Sun and The Hong Kong Case. In-depth discussion and analysis of more recent Hong Kong independent documentaries focuses on works such as Cheung King-wai's KJ: A Life in Music and films by Tammy Cheung and Evans Chan.With a particular focus on how these films address the historico-political dimension of their time, Hong Kong Documentary Film introduces students and scholars in Film Studies to this fascinating and largely unexplored cinematic tradition.